Four‐Channel Kaleidoscopic Metasurfaces Enabled by a Single‐Layered Single‐Cell Quad‐Band Meta‐Atom. Issue 3 (7th December 2021) - Xie, Rensheng; Fang, Xin; Zhang, Dajun; Wang, Xiong; Chen, Ke; An, Sensong; Zheng, Bowen; Zhang, Hualiang; Feng, Yijun; Ding, Jun
Abstract: Multichannel devices, which can manipulate multiple distinguished wavefronts like a kaleidoscope, are preferably desired for compact systems with higher integration and smaller footprint. Particularly, multiband metasurfaces are one of the intuitive and effective approaches to expand the number of the operation channels in meta‐devices. In this work, a strategy to design four‐channel metasurface based on a novel single‐cell quad‐band meta‐atom is proposed for the kaleidoscopic wavefront manipulations. While illuminating a circularly polarized wave, the independent 2π phase shifts at four distinct frequencies can be obtained by the single‐layered substrate meta‐atom with almost theoretically maximal transmission amplitudes. As a proof‐of‐concept demonstration, a four‐channel metasurface is designed to realize a single‐vortex beam generator, a dual‐vortex beam generator, a meta‐hologram, and a focusing metalens in channels 1, 2, 3, and 4, respectively. The experiment and full‐wave simulation results agree very well with each other, validating the design concept. The proposed strategy has increased the number of operation frequencies for a single‐cell meta‐atom while guaranteeing the electromagnetic performance, and may lead to advances in a variety of multifunctional devices with a compact structure such as ultra‐thin metalenses, beam generators, and holographic displays. Abstract : The four‐channel meta‐device constructed by the proposed quad‐band single‐cell meta‐atoms produces a single‐vortex beam generator, a dual‐vortex‐beam generator, a meta‐hologram, and a focusing metalens at four distinct frequencies. Furthermore, the single‐layered single‐cell quad‐band meta‐atom consists of two modified double‐C‐slot resonators and two double‐C‐shape split‐ring resonator and demonstrates the good isolation among the four resonators.